The Effect of Phase-Feeding Strategies on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs: I. Lysine Levels at the Estimated Requirement - M. B. Menegat; S. S. Dritz; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate phase-feeding strategies for grow-finish pigs under commercial research conditions and using lysine levels closely set to the pig’s requirement estimates for maximum growth performance. A total of 1,188 pigs (PIC 359 × 1050; initially 60.4 lb body weight (BW)) were used in a randomized complete block design with 27 pigs per pen and 11 pens per treatment. Treatments consisted of four feeding programs: a 1-phase feeding program with 0.82% standardized ileal digestible (SID) lysine from 60 to 280 lb BW; a 2-phase feeding program with 0.96 and 0.77% SID lysine from 60 to 220 and 220 to 280 lb BW, respectively; a 3-phase feeding program with 1.13, 0.89, and 0.77% SID lysine from 60 to 110, 110 to 220, and 220 to 280 lb BW, respectively; and a 4-phase feeding program with 1.13, 0.96, 0.82, and 0.77% SID lysine from 60 to 110, 110 to 160, 160 to 220, and 220 to 280 lb, respectively. The lysine levels were determined based on the estimated lysine requirements to achieve 100% of maximum growth rate for the weight range in each phase, using an equation developed by the genetic supplier. The experimental diets were based on corn, distillers dried grains with solubles (DDGS), and soybean meal. Overall, from d 0 to 121, pigs fed the 1-phase program had decreased (P= 0.007) average daily gain (ADG) compared to 2- and 4-phase feeding programs, with the 3-phase feeding program intermediate. There was no evidence for difference on average daily feed intake (ADFI) and feed efficiency (F/G) across the feeding programs. Final BW was lower (P= 0.050) in pigs fed the 1-phase program compared to the 4-phase program, with pigs fed 2- and 3-phase programs intermediate. Similarly, hot carcass weight (HCW) was decreased (P= 0.014) in pigs fed the 1-phase program compared to 2- and 4-phase programs, with the 3-phase program intermediate. No evidence for differences was observed across the feeding programs for carcass yield, backfat thickness, loin depth, or percentage lean. For economics, the 1-phase feeding program resulted in the lowest (P<0.001) feed cost per pig and feed cost per lb of gain, but also in the lowest (P= 0.013) revenue per pig. The 2-, 3-, and 4-phase feeding programs resulted in similar feed cost per pig, feed cost per lb of gain, and revenue per pig. The income over feed cost (IOFC) was similar across all phase-feeding programs. In conclusion, phase-feeding strategies provide advantages in growth performance over feeding a single diet throughout the grow-finish phase. However, simplification of feeding programs to two dietary phases with lysine levels closely set to requirement estimates to maximize growth performance does not compromise overall growth performance, carcass characteristics, and IOFC.
Keywords: compensatory growth; feeding regimen; finisher; nutrition; swine